Dampak Mobilitas Digitalisasi terhadap Nilai Budaya dan Perilaku Konsumtif - Widyatmoko Widyatmoko; Mahadika Pradipta Himawan; Tri Esti Rahayuningtyas; Choerul Umam (Universitas 45 Surabaya, 2025)
The development of digital technology and the intensification of societal mobility both geographic and socio relational have brought about significant changes in the cultural values ​​and consumer behavior of individuals and groups. This study uses a qualitative approach to explore how digitalization and mobility jointly and mutually influence consumer cultural values ​​and consumer behavior. Data were obtained through in-depth interviews with informants from various backgrounds who actively use digital platforms and engage in mobility changes, such as changes in residence or employment. Thematic analysis shows that digitalization accelerates the internalization of consumer norms and cross-cultural access, mobility facilitates cultural exchange and the adoption of new consumer values ​​and changes the meaning of goods as identity, and digital-mobility interactions create more flexible and rapid consumer behavior. This study suggests that cultural policies and practices should take adaptive steps in facing this transformation to maintain the sustainability of cultural values ​​and direct consumption to be more reflective.